Establishment of Prognostic Signatures of N6-Methyladenosine-Related lncRNAs and Their Potential Functions in Hepatocellular Carcinoma Patients - Wu, Xianbin; Deng, Zhejun; Liao, Xiaomin; Ruan, Xianxian; Qu, Nanfang; Pang, Lixing; Shi, Xiaoyan; Qin, Shanyu; Jiang, Haixing (Frontiers in Oncology, 2022)
N6-methylandenosine (m6a)-related mRNAs and lncRNAs have been explored their functions in several cancers. Present study aimed to identify potential signatures of m6a-related lncRNAs in hepatocellular carcinoma (HCC).We downloaded the expression and clinical data from The Cancer Genome Atlas (TCGA) database. The interacted mRNAs and lncRNAs,prognosis-related lncRNAs,potential metabolic pathways of lncRNAs,immune infiltration of various cells and CD274 (PD-L1)-related lncRNAs were analyzed. Then, in vitro experiments were explored the role of AC012073.1 (LOC105377626) in HCC cell lines. We found that candidate 14 lncRNA signatures play functions in HCC maybe by affecting immune infiltration, cell cycle, Notch signaling pathway, et al. LncRNA AC012073.1 (LOC105377626) functions as oncogenic roles in affecting HCC prognosis.